Chronic Graft Loss and Death in Patients With Post-Transplant Malignancy in Living Kidney Transplantation: A Competing Risk Analysis - Salesi, Mahmoud (Kowsar, 2014)
BACKGROUND: Malignancy is a common complication after renal transplantation. Death with functioning graft and chronic graft loss are two competing outcomes in patients with post-transplant malignancies. OBJECTIVES: The purpose of our study was to evaluate the risk factors associated with cumulative incidence of these two outcomes. PATIENTS AND METHODS: Fine-Gray model was used for 266 cases with post-transplant malignancy in Iran. These patients were followed-up from the diagnosis until the date of last visit, chronic graft loss, or death, subsequently. RESULTS: At the end of the study, as competing events, chronic graft loss and death with functioning graft were seen in 27 (10.2%) and 53 cases (19.9%), respectively, while 186 cases (69.9%) were accounted as censored. The incidence rate of death was approximately two-time of the incidence rate of chronic graft loss (8.6 vs. 4.4 per 100 person-years). In multivariate analysis, significant risk factors associated with cumulative incidence of death included age (P < 0.007, subhazard ratio (SHR) = 1.03), type of cancer (P < 0.0001), and response to treatment (P < 0.0001, SHR = 0.027). The significant risk factors associated with cumulative incidence of chronic graft loss were gender (P = 0.05, SHR = 0.37), treatment modality (P < 0.0001), and response to treatment (P = 0.048, SHR = 0.47). CONCLUSIONS: Using these factors, nephrologists may predict the occurrence of graft loss or death. If the probability of graft loss was higher, physicians can decrease the immunosuppressive medications dosage to decrease the incidence of graft loss.